Pitcairnia albifolia (Bromeliaceae), a new species from the Talamanca Mountains in Veraguas Province, Panama - Cáceres González, Daniel Adolfo; Ibáñez, Alicia (Phytotaxa, 2014)
Bromeliaceae Juss. comprises 3,348 species and 58 genera (Luther 2012), grouped in subfamilies Brocchinioideae, Bromelioideae, Hechtioideae, Lindmanioideae, Navioideae, Pitcairnioideae, Puyoideae, and Tillandsioideae (Givnish et al. 2007). According to Luther (2012), the genus Pitcairnia Ruiz & Pav. has ca. 342 species and is the most diverse in Pitcairnioideae.